Innovation of Village Financial System Application (Seskeudes) in the Perspective Of Herbert A. Stepard Theory - Sinollah - Sinollah; Mashur Hasan Bisri; Rr. Hesti Setyodyah Lestari; Imron Rosyadi Hamid (Universitas Islam Kadiri, 2023)
Village Law Number 6 of 2014 as a strategic policy for village governments to improve the welfare of village communities. The purpose of this research is to describe and analyze the innovation process of the Village Financial System (Siskeudes) in Sempu Village, Ngebel sub-district, Ponorogo Regency. To achieve these objectives, this study uses a qualitative descriptive research method with data collection techniques through observation, interviews and documentation. The results of this study indicate that judging from the process of implementing Siskeudes in Sempu Village, Ngebel sub-district, Ponorogo Regency, it has fulfilled the innovation requirements based on Herbert A. Shepard's theory which consists of: finding ideas (problem identification, information gathering, interpretation, statements and attitudes). ), adoption (socialization and modification) and application (resource preparation, personnel placement, education and training, monitoring and evaluation) of Law Number 6 of 2014 concerning Villages.